Parents' Accompanying to Identify Special-Needs Children in Depok, Indonesia. - Suharsiwi; Pandia, Weny Savitry S.; Ruwinah, Ruwinah; Yumna, Laila (Jurnal Inovasi dan Pengembangan Hasil Pengabdian Masyarakat, 2023)
The issue of detection services for children with special needs in Indonesia still merits attention, as it necessitates intensive treatment to enhance parents' ability to identify their children with growth and development issues. Regarding this topic, parents need a wealth of knowledge and skills. Community Service in Depok assists families in identifying children with special needs. Participants in the brief course must understand the characteristics of children with special needs. The goals of community service activities are as follows: a) conducting training activities on the characteristics of ABK, and b) conducting child development screening activities for the "early detection" of child growth and development issues. a) Parental comprehension of children with special needs; and b) Stage I, coordination with Forkesi, the Depok ABK service agency, the Depok Health Service, and the Depok City Government. Then, all Depok city councils and municipalities were invited to participate in parent training activities with the special parent community. The second implementation phase entails training parents on the characteristics and ABK assessment programs. The subsequent activity in Phase III was observing ABK in the classroom and exercising child development screening with our Malaysian partner, Hospital Penawar. Stage IV involves conducting a FGD with parents, instructors, and the Depok Health Service in attendance. The next step will be collaborating to monitor the Depok Posyandu Movement's developments.